Discriminação de cafés crus sadios e defeituosos por meio de espectroscopia no infravermelho médio - Ana Paula Craig Carneireiro (2011)
The objective of this work was to evaluate the potential of Fourier Transform Infrared spectroscopy (FTIR) for the characterization and discrimination of defective and non-defective coffee beans. Defective (black, immature and sour) and non-defective Arabica coffee beans were manually separated. Whole and ground coffee samples were then submitted to colorimetric analysis and FTIR analysis by transmittance readings, employing a KBr disk, and reflectance readings, employing an attenuated total reflectance (ATR) accessory (8200H/8200HA). Multivariate statistical analysis (principal component analysis - PCA and hierarchical cluster analysis - HCA) was performed in order to verify the possibility of discrimination between defective and non-defective coffee samples. The results indicated that the monochromatic color separation between defective and non defective coffee beans will only be effective in the case of black and sour defects, but not in the case of immature beans. A clear separation between defective and non-defective coffee beans was observed based on PCA and HCA analysis of the normalized spectra (ATR) and of the first derivatives of the spectra (transmittance). Spectra of non defective and green coffee were separately evaluated by PCA and were fully discriminated, demonstrating that FTIR-ATR can be employed complementary to color separation. Such results indicated that FTIR analysis presents potential for the development of a fast and reliable analytical methodology for discrimination between defective and non-defective coffee beans.